Analisis Filosofis Terhadap Hakikat Kurikulum dan Posisi Matematika dalam Implementasi Kurikulum Merdeka - Minarni Ikhrimah; Arjuna Yahdil Fauza Rambe; Mariam Nasution (Yayasan Darussalam Bengkulu, 2026)
This study aims to examine philosophically the nature of curriculum and the position of mathematics in the implementation of the Merdeka Curriculum at the junior secondary school level. This research used a qualitative approach with a case study design conducted at SMP Negeri 5 Padangsidimpuan, North Sumatra. Data were collected through classroom observations, in-depth interviews with mathematics teachers, the principal, and students, as well as documentation studies covering teaching modules, learning outcomes, school operational curriculum documents, and assessment instruments. The findings show that the implementation of the Merdeka Curriculum in mathematics learning still faces several philosophical and pedagogical tensions. First, there is an epistemological gap between the curriculum orientation that emphasizes contextual reasoning and learner autonomy and the long-standing view of mathematics as a rigid and procedural subject. Second, teachers’ understanding of the curriculum philosophy is still largely limited to technical and administrative matters. Third, the integration of the Pancasila Student Profile in mathematics learning tends to remain symbolic rather than becoming a meaningful part of the learning process. Fourth, mathematics teachers experience dilemmas related to differentiated learning, limited instructional time, varied student abilities, and assessment demands. This study concludes that the implementation of the Merdeka Curriculum requires a stronger philosophical understanding regarding the ontology, epistemology, and axiology of mathematics education. Therefore, strengthening teachers’ philosophical perspectives is important so that curriculum transformation does not stop at the level of documents but can also be reflected in classroom practices.